GEOGRAPHICAL BASIS OF LANDSCAPE AND ECOLOGICAL DEVELOPMENT OF THE MIRZACHUL REGION - Nusratulla Alimkulov (The Bioscan, 2024)
The article takes into account the theoretical aspects of natural-geographical zoning, issues of natural-geographical and geo- ecological zoning carried out in our republic, the emergence of landscape-ecological situations in the Mirzachul geosystems, the role of nosogeographical conditions in landscape-ecological zoning, types of diseases of the population and environmental protection in this case There are opinions about the geographical basis of landscape-ecological zoning.